Comparative Studies on Three Anthropophilic Blackfly Species in Ecuador as the Vector of Human Onchocerciasis - Lazo Salazar, Ramón (Revista Universidad de Guayaquil, 2013)
In the magazine “ The Japanese Journal of Parasitology “ Vol. 37, No. 2 April 1988 , was published this research work of relevance to the University of Guayaquil, Ecuador, to particípate actively in the history of Ecuadorian Onchocerciasis as reported in Journal of the University of Guayaquil No. 112 of 2012 , whose stories were reported at the International Congress of Onchocerciasis in Guatemala - Japan in 1981 , later expanding their studies in a Collaborative Research Project in Japan - Ecuador with Prof. Isao Tada . This work should have been made known , since it was part of the research the researcher Prof. Isao Tada of Japan in 1985 , inquired about of Onchocerciasis in Ecuador, proposed to with the University of Guayaquil , incorporating new research in Ecuador the project “Comparative Study Oncocercosis between South and Central America”, designating one representative per country, Ecuador, Guatemala, Venezuela . This work was published in Japan in a book of 126 pages on 1987. If by some circunstance not published research work that is part of research in Japan - Ecuador proposed by Prof. Isao Tada , accurately explain that a section of the research, published in the journal “The Japanese Journal of Parasitology” for that reason you must register the title with 4 Japanese authors reported, 3 Ecuadorian authors and two guest authors from Canadá and Spain and the residents of Ecuador, contribu[1]ted in this investigation. we consider it imperative that teachers and Ecuadorian University students get the message that only through Journal of the University of Guayaquil, it is informed fruitful work of research by the University
Keywords: Onchocerca volvulus; onchocerciasis; Simulium; transmission; vector; Ecuador